9.4k views
0 votes
If p(y) = y^3+3 y^2-5y-6, then p (-3) = ------------------

2 Answers

5 votes

Answer:

p(-3)=9

Explanation:

This question ask us to find p(-3), or what p(y) is when y is equal to -3.

We know that:

p(y)= y^3+3 y^2-5y-6

We want to find p(-3), so substitute -3 in for every y.

p(-3)= (-3^3)+3(-3^2)-5(-3)-6

Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, Subtraction.

Solve the exponents first (-3^3 and -3^2)

-3^3=-3*-3*-3= -27

-3^2= -3* -3= 9

p(-3)= -27+ 3(9) -5(-3) -6

Next, multiply 3 and 9

p(-3)= -27+27-5(-3)-6

Then, multiply -5 and -3

p(-3)= -27+27+15-6

-27 and 27 equal 0, so they cancel each other out.

p(-3)=15-6

p(-3)= 9

User Geo Angelopoulos
by
6.5k points
2 votes

Answer:

9

Explanation:


p(y)=y^3+3y^2-5y-6 \\\\p(-3)=(-3)^3+3(-3)^2-5(-3)-6= \\\\-27+27+15-6= \\\\9

Hope this helps!

User Arslan Ashraf
by
5.8k points